ANALYSIS OF SENTENCE CONNECTORS IN LYRIC SONGS OF BELIEVE ALBUM BY JUSTIN BIEBER - DARMAWATI .; FIMANDA ARLITA (LP2MTBM MAKARIOZ, 2022)
This study deals with the use of sentence connectors in believe album by Justin Bieber. The purpose of this research was toinvestigate the types of sentence connectors, explain the types of sentence connectors, and explain why and how they arethe types of sentence connectors. The data in this study was taken from the lyrics song of Justin Bieber's